Prevalence and Clinical Features of Atopic Dermatitis in China. (13th November 2016) - Wang, Xin; Li, Lin-Feng; Zhao, Da-yu; Shen, Yi-wei
Abstract : Background . The epidemiology of atopic dermatitis (AD) in Chinese outpatients is yet to be clarified. Objectives . To investigate population-based prevalence and clinical features of AD in Chinese outpatients. Methods . A multicenter cross-sectional study was conducted in outpatients with eczema or dermatitis from 39 tertiary hospitals in 15 provinces. Results . This study included 682 patients diagnosed with AD, with the mean age of 28.8 ± 20 . 1 years and the median course of 5.3 ± 6.9 years. AD patients had more severe itching (30.4% versus 13.8%, p < 0.001 ) and clinically suspected bacterial infection (21.7% versus 16.1%, p < 0.001 ) than those of other types of dermatitis. Older patients were more susceptible to have a history of flexion dermatitis (p < 0.001 ), bacterial infection (p = 0 . 005 ), and severe itching (p < 0.001 ). Outpatients with clinically suspected bacterial infection had 3.53-fold increased risk of AD than those without it (p < 0.001 ). The morbidity rate of AD in the (20–25°N) region is 2.86 times higher than that in the (40–45°N) region [OR (95% CI): 0.352 (0.241–0.514), p < 0.001 ]. Conclusions . AD is characterized by unique clinical/demographic features. Bacterial infection and latitude region may have an impact on the incidence of AD in China.